Nested PCR and the TaqMan SNP Genotyping Assay enhanced the sensitivity of drug resistance testing of Mycobacterium leprae using clinical specimens of leprosy patients. - Xiaohua Chen; Jun He; Jian Liu; Yuangang You; Lianchao Yuan; Yan Wen (Public Library of Science (PLoS), 2019)
BACKGROUND:Although leprosy is efficiently treated by multidrug therapy, resistance to first-line (dapsone, rifampin) and second-line (fluoroquinolones) drugs has been described worldwide. However, the characteristics of drug resistance in Southwest China remain unknown. Furthermore, the sensitivity of polymerase chain reaction (PCR)/sequencing for resistance detection is limited, especially for paucibacillary (PB) leprosy patients. The current study aimed to develop a nested PCR/sequencing and TaqMan SNP Genotyping Assay to increase the sensitivity of the method used to detect drug resistance in Mycobacterium leprae and to reveal the nature of M. leprae drug resistance in Southwest China. METHODOLOGY/PRINCIPAL FINDINGS:Seventy-six specimens, including skin biopsy (n = 64), formalin-fixed paraffin-embedded (FFPE) (n = 11) and skin-slit smear (SSS) (n = 1) samples from multibacillary (MB, n = 70) and PB (n = 6) leprosy patients from Southwest China, were included in this study. The presence of mutations in drug resistance-determining regions (DRDRs) of the rpoB, folP1, and gyrA genes, which are associated with rifampicin, dapsone, and quinolone resistance, respectively, was detected by PCR/sequencing, as recommended by the WHO, and the nested PCR and TaqMan SNP Genotyping Assay developed in this study. Mutations in the folP gene were detected in 19 (25.00%) samples, indicating dapsone-resistant M. leprae, with one (1.31%) sample showing mutations in two genes, folP and gyrA, reflecting multidrug-resistant strains to dapsone and ofloxacin. However, no rpoB mutation was detected. Compared with PCR/sequencing, nested PCR increased the sensitivity of detecting rpoB (from 51.39% to 78.94% for leprosy patients and from 0.00% to 50.00% for PB), gyrA (from 75.00% to 80.26% for leprosy patients and from 50.00% to 66.67% for PB), and folP1 (from 5.26% to 84.21% for leprosy patients and from 0.00% to 66.67% for PB). Moreover, the TaqMan SNP Genotyping Assay showed greater sensitivity for folP1 detection (from 5.26% to 78.94-86.84% for leprosy patients and from 0.00% to 33.33%-83.33% for PB patients) than the PCR/sequencing method. In addition, the latter method was able to more easily distinguish heterozygous genotypes and mutant homozygous genotypes from homozygous genotypes. CONCLUSIONS/SIGNIFICANCE:Nested PCR/sequencing and the TaqMan SNP Genotyping Assay are rapid and highly sensitive methods for detecting drug resistance in leprosy cases. The current study revealed that diamino-diphenylsulfone (DDS; also known as dapsone) resistance in M. leprae, as indicated by folP1 gene detection, is still the most concerning form of drug resistance in leprosy patients from Southwest China.